2020
DOI: 10.2196/20249
|View full text |Cite
|
Sign up to set email alerts
|

Learning With Virtual Reality in Nursing Education: Qualitative Interview Study Among Nursing Students Using the Unified Theory of Acceptance and Use of Technology Model

Abstract: Background Digital games–based learning is a method of using digital games to impart knowledge. Virtual reality (VR) programs are a practical application of this method. Due to demographic changes, the nursing profession will become increasingly important. These VR applications can be of use in training nurses for future professional challenges they may encounter. The continuous development of VR applications enables trainees to encounter simulated real life effectively and to experience increasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 31 publications
(49 reference statements)
4
15
0
1
Order By: Relevance
“…Fourth, the hypothesis, "there would be differences in the learning immersion between the experimental group, to whom the mechanical ventilation nursing VR simulation program was applied, and the control group, " was supported. This was consistent with the results of a previous study [32] that reported that the use of VR increased motivation for learning in the learners. For education to be delivered more effectively, we recommend employing learning materials and methods that can increase learning immersion, in parallel with simulation education for critical care nursing.…”
Section: Discussionsupporting
confidence: 93%
“…Fourth, the hypothesis, "there would be differences in the learning immersion between the experimental group, to whom the mechanical ventilation nursing VR simulation program was applied, and the control group, " was supported. This was consistent with the results of a previous study [32] that reported that the use of VR increased motivation for learning in the learners. For education to be delivered more effectively, we recommend employing learning materials and methods that can increase learning immersion, in parallel with simulation education for critical care nursing.…”
Section: Discussionsupporting
confidence: 93%
“…More and higher-quality research studies are required to explore the acceptability and effective implementation of this technology [ 11 ]. Thus far, qualitative studies have suggested easier uptake and more positive experiences among students with a high affinity toward technology [ 14 ], indicating that successful implementation relies on organizational as well as individual readiness.…”
Section: Introductionmentioning
confidence: 99%
“…Game-based learning (GBL) appears to be an alternative teaching methodology to improve the teaching-learning process, as suggested by the EESS [ 13 ]. The numerous benefits of GBL in terms of fostering student participation and creativity and improving students’ motivation when facing different subjects have been widely described [ 14 17 ]. Furthermore, the possibility of using GBL remotely is an advantage that accelerated the establishment of new methodologies when face-to-face classes on campus were restricted by the COVID-19 pandemic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%